Performance analysis of joint transmit antenna selection and user scheduling for massive MIMO systems. Issue 1 (1st January 2021) - Mengistu, Fikreselam Gared; Worku, Gizachew
Abstract: To alleviate the problem of hardware complexity, energy wastage and increased cost of deployment in massive multiple input multiple output (MIMO) system, joint antenna selection and user scheduling (JASUS) algorithms are proposed which reduce the computational complexity of optimal exhaustive search algorithm with a scarification of some spectral efficiency (SE). These algorithms remove the worst performance antenna greedily and results in best set of antennas and users at the same time. But all JASUS algorithms use semi-orthogonal user scheduling (SUS) to select users and zero forcing (ZF) precoding to mitigate co-channel interferences. A semi-orthogonal user scheduling scheme generates a high computational complexity for massive MIMO systems. Therefore, in this work with the objective of reducing the complexity of SUS, we implement two low complexity user scheduling in JASUS algorithm. These are norm-based user scheduling (NUS) and random user scheduling (RUS). Also, we apply minimum mean square error (MMSE) and maximum ratio transmission (MRT) precoding techniques along with user scheduling schemes to examine their SE and computational complexity performance when implemented in JASUS algorithm. Compared with the originally implemented SUS user scheduling technique, NUS showed a slightly better SE performance under all precoding schemes with a much reduced complexity. RUS shows around 3 bits/s/Hz performance decrement with much less computational complexity as compared to SUS in JASUS algorithm. Also, performance comparison of precoding techniques showed that MMSE results in best SE performance in most considered scenarios with all considered user scheduling schemes.